Modeling and Optimization of Extraction of Gallic Acid from Chenopodium Murale using Response Surface Methodology - Marwa Abdul Hussain Qassim (Journal of Global Pharma Technology, 2020)
In this work, the investigation of recovery of gallic acid from chenopodium mural by leaching process was conducted. 99% of ethanol was used as a solvent.  Five parameters were investigated namely time (20 - 90) min, speed of mixing (200-1000) rpm, temperature (25˚C-70˚C), particle size (100-500) µm, solid/liquid ratio 1/50 gm/gm to 1/20 gm/gm. To design the experiments, Response Surface Methodology was used using Minitab 17 software. The model equation for optimization of the extraction process was found. The best conditions for the process were extraction temperature of 70 ˚C, the liquid-solid ratio of 0.05 gm/ml, extraction time of 90 min, agitation speed of 200 rpm and particle size of 100 microns. HPLC instrument equipped with UV detector UV-20A with wavelength Range 190-700nm was used for the analysis of samples. The aim of this study is to obtain a model equation for optimization of extraction of gallic acid from Chenopodium murale using response surface methodology. The influence of temperature, solid/liquid ratio, agitation speed, particle size and time on extraction yields will analyze.Keywords: Antioxidant, Gallic acid, Chenopodium mural, Leaching and Response Surface Methodology.